ADAM and ADAMTS family proteins and their role in the colorectal cancer etiopathogenesis - Leszczynski Przemyslaw; Hendrich Andrzej Boguslaw; Szmida Elzbieta; Sasiadek Maria Malgorzata (BMB Reports, 2013)
The ADAM and ADAMTS families, also called adamalysinsbelong to an important group of extracellular matrix proteins.The ADAMs family belong to both the transmembrane andsecreted proteins, while ADAMTS family only containssecreted forms. Adamalysins play an important role in the cellphenotype regulation via their activities in signaling pathways,cell adhesion and migration. The human proteome contains21 ADAM, and 19 ADAMTS proteins, which are involved inextracellular matrix remodeling, shedding of various substratessuch as: adhesion ligands, growth factors, their receptors anddiverse cytokines. Recent studies provide evidence thatadamalysins play a crucial role in colorectal cancer (CRC)etiopathogenesis. It seems possible that adamalysins might beused as CRC prediction markers or potential pharmaceuticaltargets. [BMB Reports 2013; 46(3): 139-150]